Ryle on knowing how: Some clarifications and corrections. (27th July 2020) - Brandt, Stefan
Abstract: I argue for an account of know‐how as a capacity for practical judgment—a view I derive from Gilbert Ryle. I begin by offering an interpretation of Ryle and by correcting a number of widespread misconceptions about his views in the current debate. I then identify some problems with Ryle's account and finally present my own view which, I argue, retains Ryle's insights while avoiding his mistakes.